Origin, domestication, and genetic diversity centers of the Mexican plum, Spondias purpurea (Anacardiaceae) - Fortuny-Fernández, Norka María; Monserrat Ferrer, Miriam; Ruenes-Morales, María del Rocío (Instituto de Ecología, A.C., 2017)
Background and Aims: Conservation of wild and cultivated populations in which cultivated plants originated and were domesticated is an important management action for phytogenetic resources. The aim of this study was to identify the centers of origin, domestication and genetic diversity of Spondias purpurea in Mesoamerica through phylogeographic analyses.Methods: The trnS-trnG cpDNA marker was amplified for 66 accessions from the germplasm bank of S. purpurea and sequences from Genbank published for the genus Spondias were retrieved. Sequences were grouped in 54 populations from seven biogeographic provinces based on populations sampled, and, based on the management status of the specimens, in three categories: wild, forestry management and agricultural management.Key results: In total, 38 different haplotypes were identified, 17 were exclusive for S. purpurea, 12 to S. mombin, two to S. radlkoferi, and three to S. testudinis; one grouped both S. purpurea and S. mombin, and one both S. purpurea and S. radlkoferi. Five groups of haplotypes were identified with the nested contingency analysis for all sequences of the genus, and another five for the S. purpurea sequences.Conclusions: Analyses of the results suggest the following: 1) the lack of differentiation between the lineages may be due to hybridization between species of this genus, a hypothesis yet to be tested with other molecular markers; 2) the Western region of Mexico (Jalisco, Nayarit, Michoacán) is the center of origin; 3) the center of origin as well as Guatemala are domestication centers; 4) eight populations are particularly important for germplasm conservation programs due to the haplotypes they contain and three provinces with high nucleotide diversity.